Plugged in. (American City & County, 2006)
This article offers updates on several technology projects in the U.S. Hartford, Connecticut has contracted with Lagan to provide citizen relationship management software for the city's 311 call center that responds to non-emergency requests. The amount added by the Pennsylvania Turnpike Commission to its contract with Ciber to provide software and services for its financial computer systems is specified. The company assigned by the Bureau of Forestry in Pennsylvania to provide a spatial data management system is identified.